Racionalismo emergente: Principio activo en la humanización de la docencia universitaria (2015)
University teaching requires flexibility in generating ideas, by reasoning that they are not intended as absolute truths, but as emerging thoughts that produce dynamic to forge new knowledge interactions, as referred (Kuhn, 1986), (Morin, 2009), (Villalobos and Palencia 2013). The research purpose was approaching etnometodológicamente understand this reality at universities in Colombia, Venezuela and Mexico; the results derived from reductions and axial coding reveal prevailing analytical reasoning conceived as absolute reality, hindering innovative educational processes to guide teaching and scientific humanization by combining reason and experience (emerging rationalism).